Communication—Dissolution Measurement of Ni (111) in an Acidic Solution Using X-ray Reflectometry. Issue 6 (29th March 2017) - Ha, Hung; Fritzsche, Helmut; Burton, Gordon; Ulaganathan, Jaganathan
Abstract : The dissolution of a Ni (111) thin film exposed to a 0.1 M NaCl (pH4) solution was monitored for a period of 816 hours using X-ray reflectometry. The dissolution rate of the Ni (111) film decreased from approximately 9 Å/h at the beginning of the immersion experiment to 0.05 Å/h after 816-hour exposure. After reaching a steady state between formation and dissolution, the thickness of the NiO passive film remained constant at approximately 18 Å during the immersion experiment.